The Effectiveness of White‐Collar Crime Enforcement: Evidence from the War on Terror - Nguyen, Trung (Journal of Accounting Research, 2021)
ABSTRACT This paper analyzes the impact of changes in regulatory priorities and resource allocation on criminal enforcement of white‐collar criminal activities. Using the 9/11 terrorist attacks as a shock to the FBI's priorities and allocation of investigative resources, as well as variation in the Muslim population in the United States, I examine whether prioritization of counterterrorism investigations after 9/11 is associated with weaker enforcement of laws targeting white‐collar crime. I then use a difference‐in‐differences estimation to study the magnitude of any increase in white‐collar crime resulting from reduced oversight. I find a significantly greater reduction in white‐collar criminal cases referred by FBI field offices that shifted more of their investigative focus away from white‐collar crime to counterterrorism. Further, geographic areas in the jurisdictions of FBI field offices with greater shifts in attention from white‐collar crime to counterterrorism experienced greater increases in wire fraud, illegal insider‐trading activities, and fraud within financial institutions.